Infectious Complications in Paediatric Haematopoetic Cell Transplantation for Acute Lymphoblastic Leukemia: Current Status - Zajac-Spychala, Olga; Kampmeier, Stefanie; Lehrnbecher, Thomas; Groll, Andreas H. (Frontiers in Pediatrics, 2022)
Haematopoietic stem cell transplantation (HSCT) in paediatric patients with acute lymphoblastic leukaemia (ALL) is associated with a variety of infectious complications which result in significant morbidity and mortality. These patients are profoundly immunocompromised, and immune reconstitution after HSCT generally occurs in astrictly defined order. During the early phase after HSCT until engraftment, patients are at risk of infections due to presence of neutropenia and mucosal damage, with Gramme-positive and Gramme-negative bacteria and fungi being the predominant pathogens. After neutrophil recovery, the profound impairment of cell-mediated immunity and use of glucocorticosteroids for control of graft-vs.-host disease (GvHD) increases the risk of invasive mould infection and infection or reactivation of various viruses, such as cytomegalovirus, varicella zoster virus, Epstein-Barr virus and human adenovirus. In the late phase, characterised by impaired cellular and humoral immunity, particularly in conjunction with chronic GvHD, invasive infections with encapsulated bacterial infections are observed in addition to fungal and viral infections. HSCT also causes a loss of pretransplant naturally acquired and vaccine-acquired immunity; therefore, complete reimmunization is necessary to maintain long-term health in these patients. During the last two decades, major advances have been made in our understanding of and in the control of infectious complications associated with HSCT. In this article, we review current recommendations for the diagnosis, prophylaxis and treatment of infectious complications following HSCT for ALL in childhood.